STRATEGIES FOR IMPLEMENTING CAREER GUIDENCE IN PANDEMIC TIMES - S Sopiyah (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
In the last two years, the policy of learning from home has forced career guidance activities to be modified. Therefore, action research is carried out to prevent the occurrence of career problems and as an effort to keep career guidance running optimally. The research design used follows the action research cycle of Kemmis Mc Taggart. The research was carried out in three action cycles. The research was conducted in class XII MIA 8 with 35 research respondents. The career guidance strategy during the pandemic can be carried out in three stages of activity, namely optimizing group chat as a career information centre, assisting students in webinars conducted by universities, and holding online group guidance . Research recommends that guidance strategies still consider the principles of implementing guidance and therapeutic processes. Thus counselors must improve basic guidance skills and literacy skills so that digital career guidance helps plan a mature career